2015
DOI: 10.1152/ajpheart.00308.2015
|View full text |Cite
|
Sign up to set email alerts
|

Organic cation transporter 3 contributes to norepinephrine uptake into perivascular adipose tissue

Abstract: Watts SW. Organic cation transporter 3 contributes to norepinephrine uptake into perivascular adipose tissue. Am J Physiol Heart Circ Physiol 309: H1904 -H1914, 2015. First published October 2, 2015; doi:10.1152/ajpheart.00308.2015.-Perivascular adipose tissue (PVAT) reduces vasoconstriction to norepinephrine (NE). A mechanism by which PVAT could function to reduce vascular contraction is by decreasing the amount of NE to which the vessel is exposed. PVATs from male Sprague-Dawley rats were used to test the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 71 publications
3
33
1
Order By: Relevance
“…Since MAO‐A is located intracellularly, amines would have to enter the cell first before being metabolized. The authors demonstrated that NA uptake occurred through the extraneuronal transporter (now known as OCT3; Pizzinat et al, ), a finding further supported by functional studies showing that NA uptake in rat mesenteric resistance artery PVAT is also mediated by OCT3 (Ayala‐Lopez et al, ).…”
Section: Catecholamine Metabolism By Pvat and Adipose Tissuementioning
confidence: 86%
See 2 more Smart Citations
“…Since MAO‐A is located intracellularly, amines would have to enter the cell first before being metabolized. The authors demonstrated that NA uptake occurred through the extraneuronal transporter (now known as OCT3; Pizzinat et al, ), a finding further supported by functional studies showing that NA uptake in rat mesenteric resistance artery PVAT is also mediated by OCT3 (Ayala‐Lopez et al, ).…”
Section: Catecholamine Metabolism By Pvat and Adipose Tissuementioning
confidence: 86%
“…The uptake of NA has also been examined in IBAT where it was found to be mediated by NET (King et al, ). This is in contrast to mesenteric resistance artery PVAT, where the expression and activity of NET are low, and the transporter responsible for the uptake of NA is OCT3, present in adipocytes (Ayala‐Lopez et al, ). In IBAT, angiotensin II stimulates NA uptake, as demonstrated by the increase in [ 3 H]‐nisoxetine binding after an infusion of angiotensin II to rats (King et al, ).…”
Section: Catecholamine Uptake By Pvat and Adipose Tissuementioning
confidence: 97%
See 1 more Smart Citation
“…Using the 3T3‐L1 cells was a move to try to help us answer these questions. We isolated adipocytes from mesenteric PVAT and showed the presence of NE in these cells in ways we could not in the 3T3‐L1 cells . However, separation of adipocytes from PVAT is never perfect.…”
Section: Resultsmentioning
confidence: 82%
“…However, the similarities stop there. In rat mesenteric PVAT adipocytes, NE uptake was mainly attributed to OCT3 . The absence of mRNA for OCT3, as well as other plasma membrane transporters of NE—NET, SERT, DAT, and PMAT—suggests that NE is taken up by 3T3‐L1 adipocytes via another mechanism.…”
Section: Resultsmentioning
confidence: 98%